TNF-ɑ Induces Methylglyoxal Accumulation in Lumbar Herniated Disc of Patients With Radicular Pain - Zhang, Xinsheng; Wang, Xiaogang; Gao, Liang; Yang, Bin; Wang, Yahan; Niu, Kerun; Lai, Jiahui; Wan, Shun; Luo, Jianping (Frontiers in Behavioral Neuroscience, 2021)
Lumbar disc herniation (LDH) with radicular pain is a common and complicated musculoskeletal disorder. Our previous study showed that LDH-induced methylglyoxal (MG) accumulation contributed to radicular pain. The underlying mechanisms through which MG accumulates are poorly understood. In the present study, we found that both MG and tumor necrosis factor-alpha (TNF-ɑ) levels in the herniated disc of patients with radicular pain were significantly increased, and the activity of Glyoxalase 1 (GLO1), the rate-limiting enzyme that metabolizes MG, was decreased. In rats, the LDH model was mimicked by implantation of autologous nucleus pulposus (NP) to the left lumbar five spinal nerve root. The mechanical allodynia was observed in LDH rats. Besides, MG and TNF-ɑ levels were increased, and GLO1 activity was significantly decreased in the implanted NP. In cultured rat NP cells, stimulation with the inflammatory mediator TNF-ɑ reduced GLO1 activity and expression. These results suggested that TNF-ɑ-induced GLO1 activity decrease contributed to MG accumulation in the herniated disc of patients with radicular pain.